2014
DOI: 10.2749/101686614x13830790993762
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Control of Cable-Stayed Bridges Subject to Seismic Action

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractCable-stayed bridges are key points in transport networks and at present one of the most challenging structures for the civil engineering community. The integrity of these bridges should be guaranteed even under extremely large earthquakes. This paper begins with a discussion of the advantages of a new non-linear static "Pushover" procedure that includes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Rion-Antirion bridge, Greece). Recent studies on cable-stayed bridges with this type of connection have found that the decktower reaction significantly increases the transverse shear force and bending moment in the towers, making the transverse component of the earthquake more demanding than the longitudinal (along-deck) and vertical directions [14,15]. Indeed, the damage in the tower of the Chi-Lu bridge tower during the Chi-Chi earthquake (Taiwan 1999) can be directly attributed to the transverse response, and it is arguably the most severe seismic damage ever reported in a cable-stayed bridge [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rion-Antirion bridge, Greece). Recent studies on cable-stayed bridges with this type of connection have found that the decktower reaction significantly increases the transverse shear force and bending moment in the towers, making the transverse component of the earthquake more demanding than the longitudinal (along-deck) and vertical directions [14,15]. Indeed, the damage in the tower of the Chi-Lu bridge tower during the Chi-Chi earthquake (Taiwan 1999) can be directly attributed to the transverse response, and it is arguably the most severe seismic damage ever reported in a cable-stayed bridge [16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain F Rd , the admissible values of the structural response are set as follows: (1) the maximum admissible percentage of the input energy that is dissipated by inelastic excursions in the towers during the earthquake is considered 25% (i.e. ad m D 0:25) [21], and (2) the maximum admissible deck-tower relative displacement is set as u max d T;ad m D 1:0 m in this work, which is the distance between the deck and the tower in the transverse direction in the proposed bridges (Figure 2 (e)). The performance factor F Rd included in Table III is calculated from the results of the dynamic analysis, as discussed in the next section.…”
Section: Application Of the Proposed Design Methodsmentioning
confidence: 99%
“…The ductility of the damper ( d ) is selected in this step from a set of trial values (outer loop in Figure 1(a)). As opposed to previous design approaches in which the plate dimensions are constrained based on certain 'workable' values that indirectly limit the ductility of the damper [6,21], in this study, d is a design variable that will define the damper dimensions (Step 6).…”
Section: Design Of Dampers With Optimal Ductilitymentioning
confidence: 99%
See 2 more Smart Citations